Organochromium complexes as catalysts for the carboalumination of unactivated terminal olefins - Mark, Stefan; Gaidzik, Nikola; Doye, Sven; Enders, Markus (Dalton transactions, 2009)
The addition of aluminium alkyls to terminal olefins leads to branched organoaluminium compounds which can be converted into functionalised alkanes. This carboalumination reaction is efficiently catalysed by a donor functionalised Cp-chromium(III) complex. The active catalyst is obtained by activation of the chromium(III) dichloride precursor with MAO or with a mixture of trialkylaluminium and N,N-dimethylanilinium tetrakispentaflourphenylborate. Primary aminoalkenes deactivate the catalyst whereas secondary and tertiary aminoalkenes can also be carboaluminated.